Technological variability and raw material procurement in the Cantabrian Lower Magdalenian: Level G1 at El Cierro Cave (Ribadesella, Asturias, Spain) - Diego Herrero-Alonso; Sergio Martín-Jarque; Antonio Tarriño; David Álvarez-Alonso; Selina Delgado-Raack; Alejandro Prieto; Jesús F. Jordá Pardo; Esteban Álvarez-Fernández (Archaeological and Anthropological Sciences, 2026)
This paper presents a comprehensive analysis of the lithic assemblage from Level G1 of El Cierro Cave (northern Spain), attributed to the Cantabrian Lower Magdalenian. The study comprises 2,829 items, including 2,800 knapped artefacts, six macrolithic tools and 23 unmodified pebbles. Lithic procurement is dominated by flint, followed by quartzite and minor amounts of quartz. Eleven flint types have been identified, with local raw materials prevailing, while regional and tracer groups occur in lower proportions, indicating selective long-distance connections within the Basque-Cantabrian Basin. Technological analysis reveals complete operational chains for flake production using locally available resources, alongside greater variability in laminar reduction strategies. Blade production is limited and clearly subordinate to flake-oriented technologies. The retouched tool assemblage, dominated by endscrapers, conforms to typical Upper Palaeolithic techno-typological patterns, whereas backed bladelets are poorly represented. Use-wear analysis indicates a range of activities involving macrolithic tools, potentially linked to both lithic production and the processing of organic materials. Overall, the Level G1 assemblage at El Cierro is characterised by a strong reliance on local raw materials, restricted circulation of distant flints and low investment in laminar production, reflecting procurement strategies operating primarily at a local scale and a technological organisation adapted to domestic activities and reduced mobility.

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

When interior thermal mass helps—and when it hurts: a dynamic parametric analysis across climate, insulation, and passive use - Alejandro Cabeza-Prieto; Carmen Sánchez-Guevara; M.Soledad Camino-Olea (Energy and Buildings, 2026)

Achieving bacteria eradication on titanium implants: synergistic effect of tannic acid coating and levofloxacin - Valentina Chiara Cajiao Checchin; Alejandro Miñán; Eduardo Prieto; Natalia Soledad Fagali; Mónica Fernández Lorenzo de Mele (Biofouling, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Pseudomonas putida JM37 as a novel bacterial chassis for ethylene glycol upcycling - Francisco J. Molpeceres-García; Alejandro García-Miró; Elvira Mateos-García; Alicia Prieto; David Sanz; José I. Jiménez; Jorge Barriuso (Bioresource Technology, 2026)

Antibiofilm and osteogenic nanocoatings: a comparative study of self-assembled layers of the isomers carvacrol and thymol on titanium biomaterials - Ariel Gonzalez; Alejandro Miñán; Eduardo Prieto; Patricia Schilardi; Natalia S. Fagali; Mónica Fernández Lorenzo de Mele (Biofouling, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Mush system heterogeneities control magma composition and eruptive style on the Ocean Island of El Hierro, Canary Islands - Claudia Prieto-Torrell; Helena Albert; Meritxell Aulinas; Eloi González-Esvertit; Ilenia Arienzo; Guillem Gisbert; Valentin R. Troll; Jose-Luis Fernandez-Turiel; Alejandro Rodriguez-Gonzalez; Francisco-Jose Perez-Torrado (Contributions to Mineralogy and Petrology, 2025)
The study of recent eruptions in Ocean Islands (OIs) provides a unique window into the magma dynamics governing their plumbing systems and the mechanisms leading to eruptions. Here we present an integrated approach to unravel the dynamics of magmatic plumbing systems through detailed spatial, petrological, and geochemical characterisation of volcanic products ranging from crystal-rich ankaramitic lavas to trachytic tephras. We focus on the textural and geochemical spatial variations of 42 Holocene subaerial eruptions at the OI of El Hierro (Canary Islands), as well as on their petrogenetic significance for magmatic evolution and plumbing system architecture. Integrating geochemical data within fractional crystallisation modelling and mass balance calculations reveals that ankaramitic and porphyritic lavas with phenocryst modal abundances > 10 vol% result from melt extraction and crystal accumulation. Aphyric to sub-aphyric eruption products and porphyritic lavas with phenocryst modal abundances < 10 vol% usually follow fractional crystallisation trajectories that start at ~ 10 wt% MgO. Periodic extraction of evolved melt from crystal mushes likely led to the occurrence of minor trachytic eruptions, which are difficult to reconcile with simple closed system fractional crystallisation trends. A complex, heterogeneous crustal mush system beneath El Hierro is, in fact, the most reliable scenario to explain the wide range of textures, whole-rock and mineral compositions, and the overall surface distribution of vents and eruptive styles displayed by the Holocene volcanism on the island. Our integrated findings highlight the importance of a combined field, petrological, and geochemical study to decipher plumbing system dynamics of OI magmatism. The results allow us to put forward an updated conceptual model of the current plumbing architecture of El Hierro’s volcanic system during the Holocene.

EpiForecaster: a novel deep learning ensemble optimization approach to combining forecasts for emerging epidemic outbreaks - Milton Soto-Ferrari; Alejandro Carrasco-Pena; Diana Prieto (Stochastic Environmental Research and Risk Assessment, 2025)

In vitro toxicity of two functionalized reduced graphene oxide materials with potential application in food packaging - Óscar Cebadero-Domínguez; Leticia Diez-Quijada; Sergio López; Alejandro Prieto; María Puerto; Ana M. Cameán; Angeles Jos (Toxicology in Vitro, 2025)

In vitro evaluation of the toxicity mechanisms of two functionalized reduced graphene oxide derivatives - Óscar Cebadero-Dominguez; Leticia Díez-Quijada; María Puerto; Alejandro Prieto; Ana María Cameán; Ángeles Jos (Chemico-Biological Interactions, 2025)

First Molecular Diagnosis of Oestrus ovis (Linnaeus, 1758) Larvae Causing Conjunctival Ophthalmomyiasis in Mexico City, Mexico - Carolina Isabel Olivera-Pérez; Omar Lagunas-Calvo; Vianney Cortés-González; Alejandro Oceguera-Figueroa; Luis García-Prieto; Samuel Peña-Ortiz; Luis Alfonso Hernández-Piñamora; Miriam Erandi Reyna-Fabián (Acta Parasitologica, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Correlation of Fourier transform infrared spectroscopy data for optimizing Gramicidin production in corn kernel aqueous stream - Ksenia Lvova; Andrea Martínez-Arcos; Alejandro López-Prieto; Benita Pérez-Cid; Xanel Vecino; Ana Belén Moldes; José Manuel Cruz (Sustainable Chemistry and Pharmacy, 2024)

Life cycle assessment of a LiFePO4 cylindrical battery - Manuel Botejara-Antúnez; Alejandro Prieto-Fernández; Jaime González-Domínguez; Gonzalo Sánchez-Barroso; Justo García-Sanz-Calcedo (Environmental Science and Pollution Research, 2024)
Reduction of the environmental impact, energy efficiency and optimization of material resources are basic aspects in the design and sizing of a battery. The objective of this study was to identify and characterize the environmental impact associated with the life cycle of a 7.47 Wh 18,650 cylindrical single-cell LiFePO 4 battery. Life cycle assessment (LCA), the SimaPro 9.1 software package, the Ecoinvent 3.5 database and the ReCiPe 2016 impact assessment method were used for this purpose. Environmental impacts were modelled and quantified using the dual midpoint-endpoint approach and the “cradle-to-gate” model. The results showed the electrodes to be the battery components with the highest environmental impact (41.36% of the total), with the negative electrode being the most unfavourable (29.8 mPt). The ageing, calibration and testing process (53.97 mPt) accounts for 97.21% of the total impact associated with the production process’s consumption of energy, and 41.20% of the total impact associated with the battery. This new knowledge will allow a more detailed view of the environmental impact of cylindrical cell LiFePO 4 batteries, favouring the identification of critical points to enhance their sustainable production.

Linking metacercariae and adults of Microphallus basodactylophallus (Digenea: Microphallidae), based on larval stages from ctenophores and adult parasites from aquatic birds found in Mexico - Yeraldin Aldama-Prieto; Jorge L. Navarro-Serralde; Enrico Alejandro Ruíz; Ana L. Sereno-Uribe; Martín García-Varela (Systematic Parasitology, 2024)
Members of the genus Microphallus Ward, 1901, are endoparasites mainly of birds and mammals distributed worldwide. Unencysted metacercariae of Microphallus sp., were collected from the mesoglea of ctenophores of the genus Pleurobrachia Fleming; adult digeneans were recovered from the intestines of Eudocimus albus Linnaeus (Threskiornithidae) and Buteogallus urubitinga Gmelin (Accipitridae), in four locations from southeastern Mexico. Adult specimens were identified as M. basodactylophallus (Bridgman, 1969) based on the following features: body pyriform entirely covered by minute spines, prepharynx short, oesophagus very long, caeca short and widely divergent, testes slightly symmetrical and excretory vesicle short and V-shaped. Sequences from D1–D3 domain of the large subunit of ribosomal DNA (LSU) were generated, aligned, and compared with those of congeneric species available in GenBank. Phylogenetic analyses indicated that the metacercariae and adults formed a clade together with an isolate identified as M. basodactylophallus from Florida, USA (GenBank: AY220628). The intraspecific genetic divergence among isolates was low ranged from 0.0% to 0.6%, allowing the link between the two stages of the life cycle. We observed phenotypic plasticity in the morphological traits of M. basodactylophallus adults in definitive hosts (mammals and birds) throughout the distribution, which ranged from the USA to southeastern Mexico. Finally, the unencysted metacercariae identified as M. basodactylophallus represent the first report of a microphallid in ctenophores.

Investigating the T-stub connection with different web-to-flange joint configurations - Juan José Jiménez de Cisneros Fonfría; Ana María Gómez Amador; Alejandro Quesada González; Leopoldo Prieto Fernández (Engineering Structures, 2023)

Novel infrastructure for coral gardening and reefscaping - Sebastian Schmidt-Roach; Rebecca Klaus; Abdulaziz M. Al-Suwailem; Alejandro R. Prieto; Julian Charrière; Charlotte A. E. Hauser; Carlos M. Duarte; Manuel Aranda (Frontiers in Marine Science, 2023)
Since 1950, coral abundance has declined worldwide by an estimated 60%, and further dramatic declines are predicted. Although global reductions in carbon emissions are essential to prevent further loss, coral reef restoration has become imperative to maintain the ecosystem services that coral reefs provide to humans at local scales. Yet, currently coral restoration and gardening efforts are too expensive to scale up due to the labor-intensive nature of the methods and low success rates. Here, we present a suite of technologies that improve coral reef restoration and rehabilitation’s scalability, efficiency, and effectiveness. Our modular technologies are designed to streamline in and ex situ nursery workflows, reduce maintenance times, solve problems in transporting corals to outplanting sites, and enable rapid outplanting on natural and artificial substrates. These novel structures can act as coral seeding hubs, which placed strategically, can have the capacity to enhance coral reproduction and replenish degraded nearby reefs with larvae. They can be applied to coral restoration and reefscaping, complemented by unique eco-friendly, low-carbon-emission structures for the creation of architecturally and visually appealing habitats and underwater landscapes. Our technologies integrate novel monitoring approaches that support intelligent solutions to track genotypes, optimize and control stock management, apply assisted evolution approaches, and adaptive management through long-term monitoring.

Coupled C, H, N, S and Fe biogeochemical cycles operating in the continental deep subsurface of the Iberian Pyrite Belt - Ricardo Amils; Cristina Escudero; Monike Oggerin; Fernando Puente Sánchez; Alejandro Arce Rodríguez; David Fernández Remolar; Nuria Rodríguez; Miriam García Villadangos; José Luis Sanz; Carlos Briones; Mónica Sánchez‐Román; Felipe Gómez; et al. (Environmental Microbiology, 2023)
Microbial activity is a major contributor to the biogeochemical cycles that make up the life support system of planet Earth. A 613 m deep geomicrobiological perforation and a systematic multi‐analytical characterization revealed an unexpected diversity associated with the rock matrix microbiome that operates in the subsurface of the Iberian Pyrite Belt (IPB). Members of 1 class and 16 genera were deemed the most representative microorganisms of the IPB deep subsurface and selected for a deeper analysis. The use of fluorescence in situ hybridization allowed not only the identification of microorganisms but also the detection of novel activities in the subsurface such as anaerobic ammonium oxidation (ANAMMOX) and anaerobic methane oxidation, the co‐occurrence of microorganisms able to maintain complementary metabolic activities and the existence of biofilms. The use of enrichment cultures sensed the presence of five different complementary metabolic activities along the length of the borehole and isolated 29 bacterial species. Genomic analysis of nine isolates identified the genes involved in the complete operation of the light‐independent coupled C, H, N, S and Fe biogeochemical cycles. This study revealed the importance of nitrate reduction microorganisms in the oxidation of iron in the anoxic conditions existing in the subsurface of the IPB.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Austral Yungas under future climate and land-use changes scenarios: the importance of protected areas for long-term amphibian conservation - María Soledad Andrade-Díaz; Alejandro R. Giraudo; Gustavo A. Marás; Karl Didier; Juan Andrés Sarquis; Juan Manuel Díaz-Gómez; David A. Prieto-Torres (Biodiversity and Conservation, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Methods and approaches to advance soil macroecology - Hannah J. White; Lupe León‐Sánchez; Victoria J. Burton; Erin K. Cameron; Tancredi Caruso; Luís Cunha; Tara Dirilgen; Stephanie D. Jurburg; Ruth Kelly; Deepak Kumaresan; Raúl Ochoa‐Hueso; Alejandro Ordonez; et al. (Global Ecology and Biogeography, 2020)
Motivation and aim Soil biodiversity is central to ecosystem function and services. It represents most of terrestrial biodiversity and at least a quarter of all biodiversity on Earth. Yet, research into broad, generalizable spatial and temporal patterns of soil biota has been limited compared to aboveground systems due to complexities of the soil system. We review the literature and identify key considerations necessary to expand soil macroecology beyond the recent surge of global maps of soil taxa, so that we can gain greater insight into the mechanisms and processes shaping soil biodiversity. We focus primarily on three groups of soil taxa (earthworms, mycorrhizal fungi and soil bacteria) that represent a range of body sizes and ecologies, and, therefore, interact with their environment at different spatial scales. Results The complexities of soil, including fine‐scale heterogeneity, 3‐D habitat structure, difficulties with taxonomic delimitation, and the wide‐ranging ecologies of its inhabitants, require the classical macroecological toolbox to be expanded to consider novel sampling, molecular identification, functional approaches, environmental variables, and modelling techniques. Main conclusions Soil provides a complex system within which to apply macroecological research, yet, it is this property that itself makes soil macroecology a field ripe for innovative methodologies and approaches. To achieve this, soil‐specific data, spatio‐temporal, biotic, and abiotic considerations are necessary at all stages of research, from sampling design to statistical analyses. Insights into whole ecosystems and new approaches to link genes, functions and diversity across spatial and temporal scales, alongside methodologies already applied in aboveground macroecology, invasion ecology and aquatic ecology, will facilitate the investigation of macroecological processes in soil biota, which is key to understanding the link between biodiversity and ecosystem functioning in terrestrial ecosystems.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Physical exercise in cancer: general recommendations might not be enough - Mario Redondo; Javier S. Morales; Alejandro Lucia; Isabel Prieto (Cancer Causes & Control, 2020)

From petrographic analysis to stereomicroscopic characterisation: a geoarchaeological approach to identify quartzite artefacts in the Cantabrian Region - Alejandro Prieto; Iñaki Yusta; Alvaro Arrizabalaga (Archaeological and Anthropological Sciences, 2020)
Several isolated studies have tried to understand quartzite from an archaeological perspective by applying two different methodological approaches. The first one is based on non-destructive characterisation, aiming to understand human procurement and management of quartzite, without solid geoarchaeological criteria. The second characterised the material from archaeological sites using only petrographic or geochemical perspectives of a limited sample. Currently, both perspectives are unconnected, creating a methodological gap that needs to be solved to study the procurement and management of quartzite in greater depth. The present study, mainly methodological, will explore the gap between petrographic analysis and non-destructive characterisation. Doing so, we could fill this vacuum of information and generate a solid geoarchaeological basis to characterise not only a sample but complete assemblages. To this end, we analyse the lithic assemblages at El Arteu and El Habario, two Middle-Palaeolithic sites in the Cantabrian Region, northern Spain. We summarise the main results derived from petrographic analysis, but especially we will focus on non-destructive criteria to characterise the lithic surfaces of archaeological quartzite using stereoscope microscopy. This process allows us to understand the complete assemblage but also, through technological characterisation, understand the management of different quartzite petrogenetic types in both sites.

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

The senescence-accelerated mouse (SAM-P8) as a model for the study of vascular functional alterations during aging - Silvia Lloréns; Raquel M Melero-Fernandez de Mera; Alejandro Pascual; Ana Prieto-Martín; Yolanda Mendizábal; Carlos de Cabo; Eduardo Nava; Joaquín Jordán (Biogerontology, 2007)

Growth and survival of the pearl oyster Pinctada imbricata (Röding 1758) in supended and bottom culture in the Golfo de Cariaco, Venezuela - César Lodeiros; Damelys Pico; Antulio Prieto; Noelis Narváez; Alejandro Guerra (Aquaculture International, 2002)